2018
DOI: 10.18203/2349-3291.ijcp20182583
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of under nutrition with composite index of anthropometric failure (CIAF) among under-five children in a rural area of West Bengal, India

Abstract: INTRODUCTIONUnder-five children constitute the most vulnerable segment of any community. Their nutritional status is a sensitive indicator of community health and nutrition. Any major deviation in the nutrient intake, either in quality or in quantity from its requirement can affect growth in many ways. 1 Malnutrition among under-five children is an important public health problem in developing countries, and a major cause of morbidity and mortality in India. 2 Scarcity of suitable food, lack of purchasing powe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 4 publications
2
10
1
Order By: Relevance
“…Several studies have confirmed that girls have shown higher vulnerability in undernutrition than boys in Indian children (Bose et al 2007;Mondal and Sen 2010;Sen and Mondal 2012;Kramsapi et al 2018;Rengma et al 2016;Roy et al 2018;Debnath et al 2018). The high prevalence of undernutrition observed among children in the present investigation indicates a state of acute malnutrition which may be attributed to recent food deprivation and/or the higher prevalence of infectious diseases and socio-economic condition.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Several studies have confirmed that girls have shown higher vulnerability in undernutrition than boys in Indian children (Bose et al 2007;Mondal and Sen 2010;Sen and Mondal 2012;Kramsapi et al 2018;Rengma et al 2016;Roy et al 2018;Debnath et al 2018). The high prevalence of undernutrition observed among children in the present investigation indicates a state of acute malnutrition which may be attributed to recent food deprivation and/or the higher prevalence of infectious diseases and socio-economic condition.…”
Section: Discussionmentioning
confidence: 91%
“…Kumar (Biswas et al 2018) and 75% in Pune, Maharashtra (Rasheed and Jeyakumar, 2018). The present investigation showed that the prevalence of wasting, underweight and stunting is lower than the children of other parts of the country like the Bauri caste children (Das and Bose, 2009), urban-slum children (Dewan et al 2015), children of Agra (Agarwal et al 2014), urban children of Midnapore (Sinha and Maiti 2012), Bankura district West Bengal (Patsa and Banerjee 2018), Karbi children, Assam (Kramsapi et al 2018), Kottayam, Kerala (Jayalakshmi and Jissa 2017), Rural West Bengal (Roy et al 2018), Pune, Maharastra (Rasheed and Jeyakumar 2018), South 24 Parganas, West Bengal (Biswas et al 2018) and Yemen (Al-Sadeeq et al 2019) (Table 5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the fact that these indices have been used by many researchers for assessment of child health and nutritional status, it is still under consideration to be entitled as the finest indicator of nutritional status. An appraisal of such sort would yield practically important implications 13 .…”
Section: Introductionmentioning
confidence: 99%